Genetic Instability of (GATA) n Microsatellite DNA Repeats and Somatic Mosaicism in the Unisexual Lizards Darevskia unisexualis - Tokarskaya, O. N.; Darevsky, I. S.; Martirosyan, I. A.; Badaeva, T. N.; Korochkin, L. I.; Danielyan, F. D.; Petrosyan, V. G.; Ryskov, A. P. (Doklady. Biochemistry and biophysics, 2003)
(ProQuest: Abstract omitted; see image)[PUBLICATION ABSTRACT]